Tingkat Kepatuhan Wajib Pajak Dan Tarif Pajak: Uji Pengaruh Karakteristik Pendapatan - Puput Tri Komalasari; Moh. Nasih (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2010)
The research was intended to investigate the relationship between tax tariff and the compliance of tax payer; and how this relationship was affected by type of income (endowed income vs earned income). The degree of the tax payer compliance was measured based on reported income. The treatment of the experiment was conducted in accordance with variables of reported income (endowed v.s. earned income) and variables of tax tariff (15% vs 30%). The testing results on the impact of endowed income towards the degree of tax payer compliance indicated that there was no distinct difference on the degree of tax payer compliance towards the application of lower tax tariff of 15% as well as higher tax tariff of 30%. This premise possibly resulted from the nature of the participants as a risk averse receiving endowed income, providing that how hard they worked, they received constant amount of incomes. The testing toward participants receiving earned income revealed that they responded positively toward the increase of tax tariff by encouraging the degree of compliance to report their tax. This issue is in line with economics theory stating that tax-evasion-gamble brings higher risks whenever the tax tariff rises. Thus, the risk faced by the tax payer will increase in the line with the incline of audit and penalty probability.